Adherence to recommendations for secondary prevention medications after myocardial infarction in Estonia. (26th April 2021) - Loiveke, P; Marandi, T; Ainla, T; Fischer, K; Eha, J
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Estonian Research Council Introduction: High rates of adherence to myocardial infarction (MI) secondary prevention medications have been reported by several studies in Europe. However, results derived from unselected populations registry based data is scarce. Purpose: Aim of our study was to analyse adherence to guideline recommended medications for secondary prevention of MI of unselected patient population in Estonia in 2017-2018 and compare the results with data from 2004-2005. Methods: Population studied in 2004-2005 was based on Estonian Health Insurance Fund"s (EHIF) database and in 2017-2018 on Estonian Myocardial Infarction Registry (EMIR). EMIR is an ongoing registry recording data from all patients in Estonia diagnosed with MI (ICD-10 I21 – I22). Patients hospitalised due to MI and survived > 30 days formed the study population. By linking to EHIF"s prescription database medication adherence for angiotensin converting enzyme (ACE) inhibitors, angiotensin receptor blockers (ARB), statins, beta blockers (BB) and P2Y12 inhibitors clopidogrel and ticagrelor was assessed during one year follow-up period from first hospitalisation during period studied (at least one reimbursed prescription for the drug group during follow-up period). Results 4900 and 5067 index episodes were defined in 2004-2005 and 2017-2018, respectively. Mean age in the study population was 64.7 (+/- 11.5) and 66.5 (+/- 12.1) for men and 72.7 +/- 9.9 and 76.4 +/- 10.9 for women in 2004-2005 and 2017-2018. Rates of medication adherence among patients who survived > 30 days are presented in the Table. Conclusion: Adherence to guideline recommended medication for secondary prevention of MI in Estonia has improved considerably over 13 years. Based on our data there is room for advancement, especially among women and the elderly.